Respuesta :
Answer:
[tex]-\frac{433}{2}[/tex]
Step-by-step explanation:
Change: 2[-3(2*-1 + 3-8 + 42) - ½(20-10 - (-3))
To: 2[-3(2*-1 + 3-8 + 42) - ½(20-10+3)
Multiplication calculation: 2 * (-3 x 35) [tex]-\frac{1}{2}[/tex] * 13
Multiply again: 2 * (-105) [tex]-\frac{13}{2}[/tex]
Calculate: -210 [tex]-\frac{13}{2}[/tex]
Answer: [tex]-\frac{433}{2}[/tex]
I hope this help you! :D
Answer:
-238
Step-by-step explanation:
2(-3(2^-1+3-8+42)-1/2(20-10-(-3))=
2(-3(1/2+37)-1/2(10+3)=
2(-3(1/2+37)-1/2(13)=2(-3(75/2)-13/2)
=2(-225/2-13/2)
2(-238/2)= -238